Contextual Effect of Posyandu on the Risk of Stunting in Children Under Five, Klaten, Central Java - Mariyana, Anna; Dewi, Yulia Lanti Retno; Rahardjo, Setyo Sri (Journal of Maternal and Child Health, 2020)
Background: Stunting is a condition of failure to thrive in children under five as a result of chronic malnutrition. Environmental inter